Narratives of living through Ebola: An exploration of a Liberian community’s agency - Thompson, Esi E. (Frontiers in Communication, 2024)
The Ebola outbreak in 2014-2016 was the worst of its kind. Its end has been credited in part to community level communication and engagement. But scholarship has not focused much on community members agentic sensemaking expressions and processes during the outbreak. This study focuses on a Liberian community members' agency in their sensemaking communicative processes that constituted their lived negotiations of health and wellbeing during the Ebola epidemic. The study focuses on reconstructing the narratives and reflections of community members in disease outbreaks to show how these reveal their expressions (or suppressions) of agency and quest for survival and life sustenance. Using data from in-depth interviews and focus group discussions, the study provides a conduit for foregrounding local interpretive frames into mainstream discourses through the reinterpretations of expressions of agency. The findings suggest that community members are not agentless, but their agency is enacted within constraints preceding and exacerbated by the Ebola outbreak and expressed within existing structures and knowledge economies about culture and health. The agency of community members needs to be understood and harnessed for health communication.